PELATIHAN TEKNIS PENINGKATAN MUTU TENAGA PENDIDIK PAUD DI KOTA BALIKPAPAN KALIMANTAN TIMUR - Bety Vitriana; Lisda Hani Gustina; Suprijadi (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
Through this technical training to improve the quality of PAUD teaching staff, it is hoped that PAUD teachers can improve their ability to carry out the learning process in a more targeted, creative, innovative, and effective manner. PAUD teachers are also expected to be able to absorb new information and knowledge that will help them provide quality and high-quality education for the younger generation in Balikpapan City and its surroundings. This training was held at the Learning Activity Center (SKB Balikpapan Selatan), with the target being PAUD teachers in Balikpapan City, East Kalimantan. The method of implementing this service is: 1). Coordinate with the head of the South Balikpapan SKB as a collaborative partner of the Mulia University PAUD Study Program to facilitate activities; 2). Determine the date of implementation of the training and the main contents of the activity; 3). Prepare tools, materials, and all equipment needed for training; 4). Prepare material to be given in the movement; 5)—implementation of activities carried out in November 2022; 6). Activities include delivering material on the first day and microteaching practice on the second. The results of implementing this service have a good impact on PAUD educators and provide skills to PAUD teachers in dealing with children who have to learn problems and improve the quality and quality of human resources at the PAUD unit level. The results of this community service also increase the relationship between Mulia University, especially the PAUD Study Program, with institutions outside the campus, such as the South Balikpapan SKB and PAUD Schools, that attend this training.